Kadar VFA Dan N-NH3 Domba Lokal Yang Diberi Pakan Mengandung Ekstrak Bunga Waru (Hibiscus tilisceus) Dengan Bahan Pembawa Yang Berbeda Secara In Vitro - Purwanto, Tono; Bata, Muhammad; Rahayu, Sri (ANGON: Journal of Animal Science and Technology, 2019)
Background. The purpose of the research was to study the effect of carrier and Hibiscus tiliaceus flower extract on VFA and N-NH3 rumen production of local sheep. Materials and Methods. The feed ingredients used were rice straw ammoniation and concentrate with dry matter ratio of 40:60. The method used experiment designed according to completely randomized design (CRD) of Factorial pattern of 2x3. There were two factors used in this research. The first factor was the carrier of rice bran (DP) and tofu byproduct (AT). The second factor were the three dosage of extract. Thereore, there were six combination used as treatments. Results. The results showed that there was an interaction tendency (P<0,057) between Hibiscus tiliaceus flower extract and carrier on VFA production. However it was not significant effect (P>0,05) on N-NH3 production. Both carrier and dousage had significant effect (P<0,05) on VFA levels, while, N-NH3 did not effect (P>0,05). Orthoghonal polynomial test showed that increasing of Hibiscus tiliaceus extract caused enhancing of VFA production quadratically and the highest VFA production achieved at 60 ppm with rice bran as carrier. Conclusion. The dosage of 60 ppm of Hibiscus tiliaceus extract with rice bran carrier produced highest of VFA production.